Spatial and phenotypic heterogeneity of resident and monocyte-derived macrophages during inflammatory exacerbations leading to pulmonary fibrosis - Moos, Philip J.; Cheminant, Jenna R.; Cowman, Sophie; Noll, Jessica; Wang, Qiuming; Musci, Teresa; Venosa, Alessandro (Frontiers in Immunology, 2024)
Genetic mutations in critical nodes of pulmonary epithelial function are linked to the pathogenesis of pulmonary fibrosis (PF) and other interstitial lung diseases. The slow progression of these pathologies is often intermitted and accelerated by acute exacerbations, complex non-resolving cycles of inflammation and parenchymal damage, resulting in lung function decline and death. Excess monocyte mobilization during the initial phase of an acute exacerbation, and their long-term persistence in the lung, is linked to poor disease outcome. The present work leverages a clinical idiopathic PF dataset and a murine model of acute inflammatory exacerbations triggered by mutation in the alveolar type-2 cell-restricted Surfactant Protein-C [SP-C] gene to spatially and phenotypically define monocyte/macrophage changes in the fibrosing lung. SP-C mutation triggered heterogeneous CD68 + macrophage activation, with highly active peri-injured cells relative to those sampled from fully remodeled and healthy regions. Ingenuity pathway analysis of sorted CD11b -SigF + CD11c + alveolar macrophages defined asynchronous activation of extracellular matrix re-organization, cellular mobilization, and Apolipoprotein E (Apoe) signaling in the fibrosing lung. Cell-cell communication analysis of single cell sequencing datasets predicted profibrogenic signaling (fibronectin/Fn1, osteopontin/Spp1, and Tgfb1) emanating from Trem2/TREM2 + interstitial macrophages. These cells also produced a distinct lipid signature from alveolar macrophages and monocytes, characterized by Apoe expression. Mono-and di-allelic genetic deletion of ApoE in SP-C mutant mice had limited impact on inflammation and mortality up to 42 day after injury. Together, these results provide a detailed spatio-temporal picture of resident, interstitial, and monocyte-derived macrophages during SP-C induced inflammatory exacerbations and end-stage clinical PF, and propose ApoE as a biomarker to identify activated macrophages involved in tissue remodeling.